Perencanaan Turbin Air Kapasitas 2 x 1 MW di PLTM Cianten 1 Kabupaten Bogor - Asrori .; Eko Yudiyanto (Jurnal Energi dan Teknologi Manufaktur, 2018)
Minihidro Cianten 1 Power Plant (PLTM C-1) capacity 2 x 1 MW, located in Cianten river, Cibunian village, Pamijahan district, Bogor district. Preliminary planning data is with design head (Hd) = 27.7 m, design discharge per unit (Qd) = 4.0 m3 / s, power house elevation = +529,0 m. Turbine planning includes calculation of rated power output, type selection and number of turbines, specific speed velocity and runaway speed, runner diameter, turbine elevation setting, spiral casing and draft tube dimensions and pre-powerhouse design. Turbine performance and stability including pressure rise, speed rise and weighted average efficiency are also planned. Planning is based on calculations from international standard hydro powerplant planning guidance. The results of the calculations are verified by software and catalog of turbine manufacturers. The turbine specification results are as follows: 2 horizontal francis units, rated output power / unit (Pr) = 1000 kW (1 MW), turbine spin (n) = 600 rpm, turbine efficiency (T) = 0.92, (ns) = 298.6 rpm (M-kW), runaway speed = 1219 rpm, runner diameter = 0.769 m, runner weight (WR) = 294.05 kg, total turbine weight (WT) = 3060,37 kg. The stability of turbine operation is declared safe where the value of speed rise and pressure rise are 44.39% and 19.39% respectively. While the performance as a warranty from turbine manufacturers expressed with the value of weighted average efficiency of 88.67%.